(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Iodine deficiency disorders (IDD) are common nutritional problem globally. All groups of people are affected by it, but the pregnant women and their neonates are most vulnerable. Objectives: This study was carried out to see the iodine status of pregnant women using median urinary iodine concentration (MUI) as a measure of outcome. Methods: This cross sectional observational study assessed the MUI in casual urine samples from 225 pregnant women (75 pregnants from each trimester) and 75 non-pregnant healthy controls. The urinary iodine content was estimated in urine sample using the method of Dunn et al. with the modification of Sandell & Kolthoff (wet digestion method). Results: Median value of urinary iodine in pregnant women was 48.21Ug/L compared to 52.27